High-Dose Antibiotics in Intensive Care: A Review of Their Role in Combatting and Contributing to Antimicrobial Resistance - Galo G. Farfán-Cano; Carlos R. Cedeño-Cevallos (Microbes, Infection and Chemotherapy)
Introduction. High-dose antibiotic regimens are commonly employed to improve outcomes in critically ill patients with severe infections; however, their direct impact on antimicrobial resistance (AMR) remains underexplored. Methods. This systematic review analyzed randomized controlled trials (RCTs) published between 2020 and 2024, focusing on high-dose regimens for gram-negative bacterial infections, cellulitis, and ventilated hospital-acquired bacterial pneumonia (vHABP). A comprehensive search was conducted using the Web of Science and PubMed databases, yielding four studies that met the inclusion criteria. Results. The results suggest that while high-dose regimens reduce treatment failure and improve clinical outcomes, they are associated with higher adverse effects and may contribute to antibiotic-resistant bacteria. Notably, none of the studies directly assessed the molecular or epidemiological mechanisms linking high-dose regimens to AMR, underscoring a significant gap in the current literature. Conclusion. Further research is required to elucidate these mechanisms and establish evidence-based guidelines that balance immediate clinical benefits with long-term public health concerns.